Support recycling in additive manufacturing: A case study for enhanced wear performance of Ti6Al4V alloy. (July 2023) - Yamanoglu, Ridvan; Bahador, Abdollah; Kondoh, Katsuyoshi
The production of metals by additive manufacturing is developing rapidly. After production, support structures emerge as waste materials. In this study, Ti6Al4V support structures recycled from the selective laser melting process were consolidated by vacuum hot pressing. Spherical and irregularly shaped Ti6Al4V alloy particles were also used for the comparison as raw materials. All raw materials have been subjected to the same sintering process by hot pressing. The microstructures of the samples were carried out, and their dry sliding wear performance was studied. The samples produced from support structures showed the highest wear performance compared to the powder forms of raw materials. This study showed that the support structures from additive manufacturing could be recycled and transformed into full dense structures by pressure-assisted sintering techniques, and enhanced wear performance can be obtained.